Vaginal Reconstruction with Pudendal Thigh Flap- an early experience in Shaheed Sohrawardi Medical College Hospital (Bangladesh Journal of Plastic Surgery, 2011)
The surgical management of the absence of the vagina is a complex problem and constitutes a significant technical  challenge. The aim is to create a neovagina that is satisfactory both functionally and aestheticaly using a technique that is simple, reliable, and applicable to most patients. Earlier techniques used were skin grafts, or local skin  flaps with various degrees of success. Tissue expanders and vascularized flaps like gracilis myocutaneous flaps  were used for more extensive reconstruction. In 1989 Wee and Joseph introduced a new technique using bilateral  pudendal thigh flaps based on post labial artery; a branch of perineal artery, which itself is the continuation of  the internal pudendal artery. A 16 year old girl with congenital vaginal stenosis in whom previous two attempts of  vaginal recanalization have failed, a neovagina was created using the bilateral pudendal thigh flaps, the lining of the cavity was made by the fasciocutaneous flap with the blood supply from the posterior labial artery, a branch of perineal artery. There was no per-operative or post operative complications. Follow-up shows no significant  contractions, the reconstructed vagina is expansible and post operative stenting or dilatation was not required.  There is good sensation in the wall of the constructed vagina because sensory nerves run through the flaps. Key words: Vaginal stenosis; Neo-vagina; Pudendal Thigh Flaps. DOI: http://dx.doi.org/10.3329/bdjps.v1i2.8798 BDJPS 2010; 1(2): 3-9